Tryptophan intake is related to a lower prevalence of depressive symptoms during pregnancy in Japan: baseline data from the Kyushu Okinawa Maternal and Child Health Study - Miyake, Yoshihiro; Tanaka, Keiko; Okubo, Hitomi; Sasaki, Satoshi; Arakawa, Masashi (European journal of nutrition, 2022)
Objective Tryptophan is an essential amino acid wholly derived from diet. While the majority of tryptophan is degraded through the kynurenine pathway into neuroactive metabolites like quinolinic acid and kynurenic acid, a small proportion of ingested tryptophan is metabolized into the neurotransmitter serotonin. The current cross-sectional study in Japan examined the association between tryptophan intake and depressive symptoms during pregnancy. Methods Study subjects were 1744 pregnant women. Dietary intake during the preceding month was assessed using a self-administered diet history questionnaire. Depressive symptoms were defined as a score ≥ 16 on the Center for Epidemiologic Studies Depression Scale. Adjustment was made for age, gestation, region of residence, number of children, family structure, history of depression, family history of depression, smoking, secondhand smoke exposure at home and at work, employment, household income, education, body mass index, and intake of saturated fatty acids, eicosapentaenoic acid plus docosahexaenoic acid, calcium, vitamin D, and isoflavones. Results The prevalence of depressive symptoms during pregnancy was 19.2%. After adjustment for confounding factors, higher tryptophan intake was independently inversely associated with the prevalence of depressive symptoms during pregnancy: the adjusted prevalence ratios (95% confidence intervals) for depressive symptoms during pregnancy in the first, second, third, and fourth quartiles of tryptophan intake were 1 (reference), 0.99 (0.76−1.28), 0.94 (0.71−1.25), and 0.64 (0.44−0.93), respectively ( p for trend = 0.04). Conclusions Higher estimated tryptophan intake was cross-sectionally independently associated with a lower prevalence of depressive symptoms during pregnancy in Japanese women.